2016
DOI: 10.1038/ncomms11366
|View full text |Cite
|
Sign up to set email alerts
|

PDE6δ-mediated sorting of INPP5E into the cilium is determined by cargo-carrier affinity

Abstract: The phosphodiesterase 6 delta subunit (PDE6δ) shuttles several farnesylated cargos between membranes. The cargo sorting mechanism between cilia and other compartments is not understood. Here we show using the inositol polyphosphate 5′-phosphatase E (INPP5E) and the GTP-binding protein (Rheb) that cargo sorting depends on the affinity towards PDE6δ and the specificity of cargo release. High-affinity cargo is exclusively released by the ciliary transport regulator Arl3, while low-affinity cargo is released by Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
108
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 44 publications
(86 reference statements)
3
108
0
Order By: Relevance
“…INPP5E showed an approximately 100 fold higher binding affinity to PDE6d with a dissociation constant in the nanomolar range as compared to submicromolar affinities for Ras and Rheb. 46 Stimulated by the findings that only Arl3 can release high affinity ciliary cargo from Unc119 12,15 and from PDE6d, 38 we could confirm that under identical concentrations only Arl3 is able to release a C-terminal prenylated INPP5E peptide from its complex with PDE6d, while Arl2 did not. 46 Kinetic studies showed that the stimulated release of farnesylated INPP5E peptide by Arl3 GTP is 600fold faster than by Arl2 GTP.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 76%
See 4 more Smart Citations
“…INPP5E showed an approximately 100 fold higher binding affinity to PDE6d with a dissociation constant in the nanomolar range as compared to submicromolar affinities for Ras and Rheb. 46 Stimulated by the findings that only Arl3 can release high affinity ciliary cargo from Unc119 12,15 and from PDE6d, 38 we could confirm that under identical concentrations only Arl3 is able to release a C-terminal prenylated INPP5E peptide from its complex with PDE6d, while Arl2 did not. 46 Kinetic studies showed that the stimulated release of farnesylated INPP5E peptide by Arl3 GTP is 600fold faster than by Arl2 GTP.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 76%
“…46 Stimulated by the findings that only Arl3 can release high affinity ciliary cargo from Unc119 12,15 and from PDE6d, 38 we could confirm that under identical concentrations only Arl3 is able to release a C-terminal prenylated INPP5E peptide from its complex with PDE6d, while Arl2 did not. 46 Kinetic studies showed that the stimulated release of farnesylated INPP5E peptide by Arl3 GTP is 600fold faster than by Arl2 GTP. 46 Structural and biochemical analysis of Arl2/3 complexes with PDE6d and Unc119 showed that the major determinant for this difference is the structure and dynamics of the N-terminal amphiphatic helix which is absolutely required for the release activity of Arl3.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 76%
See 3 more Smart Citations